2005
DOI: 10.1007/s00280-005-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

GBP1 overexpression is associated with a paclitaxel resistance phenotype

Abstract: In the search for novel genes involved in the paclitaxel resistance phenotype, prior studies of gene expression in paclitaxel-resistant cell lines and their paired drug-sensitive parental lines using high-density Affymetrix GeneChip arrays identified guanylate-binding protein 1 (GBP1) gene as an overexpressed transcript. The GBP1 gene encodes a large GTPase that is induced by interferon gamma (IFN-gamma) in a variety of eukaryotic cells. In this report we characterize GBP1 and demonstrate that GBP1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 28 publications
4
68
0
1
Order By: Relevance
“…The MTT assay showed (RELB, NFκB2, IL1, FGF1, FGF5, EGR1), p53 signaling pathway (CyclinG 2 , IGFBP3, SERPIN1), Toll receptor (TLR4, NFκB2, PTGS2, TNFAIP3, RELB), TGFbeta (ID2, FKBP1B), a closely associated coagulation and plasminogen activation cascades (F3, PLAUR, C3, SERPINE1, MMP13, SERPINB2) and steroid hormone biosynthesis (CYP1B1, ALDH3A2). A set of genes with an established role in multidrug and/or taxane specific resistance was also found and included GBP1, 6 Serpin1 and SerpinB2, CXCL5, AKAP12, 7 LAMC2, 8 as well as TGFβI 9 all of which were constitutively downregulated in PC-3 cell clones. Exception was a constitutively upregulated tubulin α1, a member of the tubulin family of microtubule proteins, the target for docetaxel binding and a well established taxane resistance mediator.…”
Section: Validation Of the Gene Array Results By Quantitative Realtimmentioning
confidence: 99%
See 2 more Smart Citations
“…The MTT assay showed (RELB, NFκB2, IL1, FGF1, FGF5, EGR1), p53 signaling pathway (CyclinG 2 , IGFBP3, SERPIN1), Toll receptor (TLR4, NFκB2, PTGS2, TNFAIP3, RELB), TGFbeta (ID2, FKBP1B), a closely associated coagulation and plasminogen activation cascades (F3, PLAUR, C3, SERPINE1, MMP13, SERPINB2) and steroid hormone biosynthesis (CYP1B1, ALDH3A2). A set of genes with an established role in multidrug and/or taxane specific resistance was also found and included GBP1, 6 Serpin1 and SerpinB2, CXCL5, AKAP12, 7 LAMC2, 8 as well as TGFβI 9 all of which were constitutively downregulated in PC-3 cell clones. Exception was a constitutively upregulated tubulin α1, a member of the tubulin family of microtubule proteins, the target for docetaxel binding and a well established taxane resistance mediator.…”
Section: Validation Of the Gene Array Results By Quantitative Realtimmentioning
confidence: 99%
“…These experimental conditions were sought to help a prominent mediator of paclitaxel resistance. 6 We found that the ectopic overexpression of GBP1 using cDNA plasmid constructs notably increases docetaxel sensitivity. Altogether, our studies suggested existence of different, complex and likely complementary molecular mechanisms mediating resistance to docetaxel and suggested new potential target leads for future investigations.…”
Section: Gene Expression Profiling Of the Androgen Independent Prostamentioning
confidence: 99%
See 1 more Smart Citation
“…The only cellular interaction partner of GBP-1 known so far is b-IIITubulin (14). This points to interaction of GBP-1 with structural proteins and suggests that overexpression of GBP-1 in paclitaxel-resistant cells is directly associated to the therapeutic failure of this antimitotic drug in certain tumors (15).…”
mentioning
confidence: 99%
“…hGBP1 also has been shown to negatively regulate expression of matrix metalloproteinase 1 in endothelial cells, leading to reduced invasive capabilities of the cells into collagen I matrices (22). Additionally, hGBP1 expression has been associated with paclitaxel resistance in ovarian cancer cell lines (23).…”
mentioning
confidence: 99%